The Influences Of Transformational Leadership, Motivator Factor, And Hygiene Factor Toward Job Satisfaction Of Balai Besar Latihan Ketransmigrasian Yogyakartaâs Employee - Pangesti, Galuh Rahmi; Tjahjono, Heru Kurnianto; Maryati, Tri (Jurnal Bisnis Teori & Implementasi)
This research aims to know and analyze whether transformational leardership, motivator factor, and hygiene factor influence job satisfaction to the employee of Balai Besar Latihan Ketransmigrasian Yogyakarta. It is also objected to know variable and factors having an effect on most dominant to employee`s job satisfaction at Balai Besar Latihan Ketransmigrasian Yogyakarta. The research method applied is descriptive analiytical method and multiple regression analytical method and using the SPSS version15.00 software as processing data. Primary data are acollected by distributing questionnairesin which variables are measured by Likert scale. The result of this research indicates that independent variablese.gÂ transformational leardership, motivator factor, and hygiene factor are simultaneously and partially having significant influences to variable dependent that is job satisfaction. The result of this research also indicates that hygiene factor is the most dominant variable that influencestheir job satisfaction. Based on determinant identification, it shows that adjusted RÂ²Â is 72,5%, meaning that employeesâ job satisfaction of Balai Besar Latihan Ketransmigrasian Yogyakarta is affected simultaneously and partially by transformational leardership, motivator factor, and hygiene factor and 27,5% effected by other variables that have not been used in this research.